The spiritual dynamics of chronic post traumatic stress disorder - McBride, J. Lebron (Journal of religion and health, 1995)
Although there have been numerous articles and books written about Post Traumatic Stress Disorder (PTSD), relatively little has been written about the spiritual dynamics of this disorder. The authors of this article suggest that the spiritual components of PTSD should be addressed in treatment because they may have profound impact on chronic PTSD patients. A framework for treatment involving eight RsRisking and Revealing, Responding and Releasing, Reflecting and Reconciling, and Resurrecting and Rebuildingis described.